White House nominates Delphin‐Rittmon, for SAMHSA head. Issue 17 (1st May 2021) - Knopf, Alison
Abstract : Miriam E. Delphin‐Rittmon, M.D., since 2015 the commissioner of the Connecticut State Department of Mental Health and Addiction Services, was nominated to be assistant secretary for mental health and substance use at the federal Department of Health and Human Services by the White House last week. In her role as SSA (Single State Authority), Delphin‐Rittmon has been committed to promoting recovery‐oriented, integrated and culturally responsive services and systems that foster dignity, respect and meaningful community inclusion. In addition, through her 20‐year career in the behavioral health field, Delphin‐Rittmon has extensive experience in the design, evaluation and administration of mental health, substance use and prevention services and programs, and has received several awards for advancing policy in these areas. Most recently, she received the 2019 State Service Award from the National Association of State Drug and Alcohol Directors and the 2016 Mental Health Award for Excellence from the United Nations Committee on Mental Health.